Pidana Dalam Hukum Islam Dan Perbandingan Dengan Hukum Pidana Nasioual - teguh prasetyo (Fakultas Hukum Universitas Islam Indonesia, 2005)
The traditional criminal which originates from Isiamic Fiqh has a great philosophical basic to be the source of the national criminal law reform in Indonesia. However, it is relevant to seeks the religious values to establish the new Criminal Law.